Penicillamine ameliorates intestinal barrier damage in dextran sulfate sodium-induced experimental colitis mice by inhibiting cuproptosis - Ma, Jiaze; Ma, Yimeng; Wang, Shuangshuang; Tang, Wenwen; Chen, Chen; Li, Yang; Chen, Yugen; Chen, Tuo (Frontiers in Immunology, 2025)
BackgroundCuproptosis is a copper-dependent form of cell death. However, its role in ulcerative colitis (UC) remains unknown.AimTo investigate whether cuproptosis is involved in UC and whether penicillamine (PA) improves colitis in mice by inhibiting cuproptosis.MethodsWe analyzed the expression of cuproptosis-related genes in patients with UC using the Gene Expression Omnibus database. We used dextran sulfate sodium (DSS) to establish an experimental model of UC and explore the effects of cuproptosis on the intestinal barrier. Mice were treated with the copper-depleting agent tetrathiomolybdate to establish causality between cuproptosis and intestinal barrier damage in mice with DSS-induced colitis. We assessed the effects of PA on the intestinal barrier in mice with DSS-induced colitis. Key methodologies included copper quantification using inductively coupled plasma mass spectrometry and rubeanic acid histochemical staining, along with the analysis of cuproptosis-related and barrier proteins using qRT-PCR, immunoblotting, immunohistochemistry, and immunofluorescence.ResultsCuproptosis was closely related to intestinal barrier damage in patients with UC and in DSS-induced colitis mice, characterized by increased copper levels and dihydrolipoamide S-acetyltransferase (DLAT) oligomerization and reduced Fe-S cluster-containing proteins ferredoxin 1 (FDX1) and lipoyl synthase (LIAS) levels. Copper depletion ameliorated disease-related manifestations in mice with colitis, mitigated the aberrant expression of pro-inflammatory factors, and concurrently enhanced the expression of tight junction proteins. PA inhibited cuproptosis in the intestinal barrier of mice with colitis by reducing excess copper levels and DLAT oligomerization, as well as rescuing the loss of FDX1 and LIAS.ConclusionCuproptosis is involved in UC pathogenesis. The identification of PA, which inhibits cuproptosis in the intestinal barrier of mice with colitis, provides a novel therapeutic option for the clinical management of UC.